A Process of Recovery of a Natural Yellow Colourant from Opuntia Fruits - José A. Fernández-López; Pedro J. Giménez; José M. Angosto; Juan I. Moreno (Food Technology and Biotechnology, 2012)
This paper focuses on the development of a processing scheme to obtain a water-soluble natural yellow colourant from Opuntia fruits for application in food, paying special attention to the extraction procedure. Edible yellow Opuntia fruits grown in Murcia (Spain) were homogenized and extracted with ethanol, water, or ethanol/water (60:40) solvents. Pigment extract was chemically characterized and individual pigments were identified by high-performance liquid chromatography (HPLC), UV-VIS spectrophotometry, and electrospray ionization mass spectroscopy. A sequential extraction procedure was determined as follows: homogenization, stirring, centrifugation, filtration and concentration. The highest betaxanthin content per kg of fresh pulp (0.68 mmol of indicaxanthin) was obtained from the hydroalcoholic extract, and moreover, this solvent minimized the presence of mucilage and pectins, which are substances not desired in dye extracts. A concentrated pigment extract was obtained under rotary evaporation at 35 °C and reduced pressure (6 kPa), with a betaxanthin concentration (expressed as indicaxanthin) of 0.27 g/L, and CIELAB values of L*=92.7, a=–0.8 and b*=68.5. The individual pigment HPLC analysis with photodiode array and mass spectral detection revealed that proline-betaxanthin (indicaxanthin) was clearly dominant, while all other betalains were present in comparatively low quantities. The pigment stability was checked at 4 and 25 °C. Kinetics analyses indicate that the betaxanthin degradation pattern can be approximated as pseudo-first-order kinetics.